Differences in oxygen consumption, reproduction, feeding, and growth of the freshwater cyclopoid copepod Cyclops vicinus (Uljanin, 1875), infected with a cestoda procercoid - Dörücü, M (Brill, 2002)
Differences in body size and oxygen consumption were found between uninfected individuals of the freshwater cyclopoid copepod Cyclops vicinus (Uljanin) and those infected with a Cestoda procercoid (P < 0.05). Oxygen consumption and growth were lower in infected copepods. A reduction in the reproductive capacity of infected females was observed. Although 68% of uninfected female Cyclops had developed eggs in their gonads, only 25% of the infected female copepods had developed eggs. The feeding rate of infected copepods was, on the contrary, relatively high.
Keywords: Behavior; Host